Legislative significance of custom in developing local family fiqh: an analysis of its conceptual framework - Haneef, Sayed Sikandar Shah; Fatah Yasin, Raudlotul Firdaus; Ijaz, Rabia (2020)
Islamic jurisprudence though originates in divine revelation is elastic enough to assimilate local customs and social norms in accordance with its own terms and conditions to preserve its divinity (sanctity).With the advent of new trends of thought in the field of legal hermeneutics and advocacy for historical–cum-sociological approaches to study religious texts, an erroneous conclusion has been made that Islamic law is nothing but a set of rules concocted by juristic conniving to rubber stamp social realities of their times. In this context, any overemphasis on the legislative place of `urf by Muslim legal scholars is also cited as pieces of evidence to cast more skepticism about the revealed genre, content, and structure of Islamic law. The advocacy for local fiqh with its pious intention needs to take notice of such dangers so as not to fall into such traps by going overboard and regarding the bulk of the fiqh corpus as historical and time-space bound. To avert such a folly, it is deemed to reflect back on the true meaning and correct use of `urf as a tool for local fiqh construction. According, this study by adopting a content analysis method argues that `urf in the Islamic legal thought supplements revealed laws and never abdicates them.